Weed Management During Pasture Establishment - Brent Sellers; Jason Ferrell; Joao Vendramini; Yoana Newman (EDIS)
SS-AGR-287, a 2-page fact sheet by Brent Sellers, Jason Ferrell, Joao Vendramini, and Yoana Newman, details techniques for chemical weed control prior to and during pasture establishment in Florida. Published by the UF Department of Agronomy, October 2007.